PERSEPSI ORANG TUA TERHADAP IMPLEMENTASI PROGRAM MAKANAN BERGIZI GRATIS (MBG) DI TK IMMANUEL KIDS - Rachel Theresia Natanael Tambun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Nutritional problems in early childhood remain a critical issue in Indonesia, characterized by high prevalence of stunting and wasting. The Free Nutritious Meal Program (MBG), launched on January 6, 2025 by the Indonesian government under President Prabowo-Gibran, represents a strategic intervention to address nutritional deficiencies, targeting 82.9 million beneficiaries including preschool children. This study aims to analyze parental perceptions of MBG implementation at TK Immanuel Kids, Medan. Using a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews with 10 parents conducted from April 13-17, 2025. Perceptions were analyzed across three dimensions: cognition, affection, and conation. Findings reveal that while most parents were aware of the program through school WhatsApp groups, their depth of understanding varied considerably. Affective responses ranged from positive (feeling helped and reassured) to negative (concerns over food quality, hygiene, and menu suitability). In terms of conation, the majority offered conditional support supplementing nutrition at home while voicing concerns about food quality consistency and menu variation. The study concludes that MBG at TK Immanuel Kids shows promising potential but requires improvements in food quality consistency, menu diversity, and transparent communication between school and parents to maximize program effectiveness.